4-substituted tert-butyl phenylazocarboxylates-synthetic equivalents for the para-phenyl radical cation - Höfling, Sarah; Bartuschat, Amelie; Heinrich, Markus (Angewandte Chemie International Edition, 2010)
First electrophile, then radical: 4-Substituted tert-butyl phenylazocarboxylates 1 are versatile synthetic equivalents of the para-phenyl radical cation 2. The tert-butyloxycarbonylazo group enables nucleophilic substitutions to proceed under mild conditions and can later be employed for the generation of aryl radicals. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: arenes; aromatic substitution; nucleophilic substitution; radical reactions; synthetic methods